PENYELENGGARAAN PENCAPAIAN TARGET KINERJA DINAS PENDIDIKAN DAN KEBUDAYAAN PROVINSI JAWA TENGAH - Widyaka Satriayudha Pradana; Nina Widowati (Journal of Public Policy and Management Review, 2018)
Every Organization surely will set their work performance to carry out their tasks and function targets, in those schemes needs various instruments that are capable of becoming an essential. The purposes of this paper are to describe and analyze the work performance, and also to identify the factors that affected work permormance of Dinas Pendidikan dan Kebudayaan Provinsi Jawa Tengah. This paper uses the organization work performance measurement theory by Bernadin to analyze the work performance of Dinas Pendidikan dan Kebudayaan Provinsi Jawa Tengah by the approach of quality, quantity, timeliness, and costeffectiveness. The research design that is used by this paper is qualitative research design with descriptive approach. The Datas in this paper are collected by documentation study, observation method, interview, and literature study. The result of this paper is, there are three dimensions out of four that show positive results. They are quality dimension, quantity dimension, and cost-effectiveness dimension. While there is one dimension that shows negative result, it is timeliness dimension. There are two factors that affect the work performance is the support workers and technology. The writer suggests that, need a routine evaluation of each month reporting related to monitoring the implementation of activities and a budget to match the absorption time specified. It is also necessary to implement reward and punishment scheme in order to assert that Dinas Pendidikan dan Kebudayaan Provinsi Jawa Tengah has been serious in implementing the reporting, and also need to maximize Rencana Kerja Operasional (RKO) as real monitoring tool in accordance with the plans that have been drawn up at the beginning of the period